Clinical outcomes of complete versus incomplete revascularization in patients treated with coronary artery bypass grafting: insights from the TiCAB trial. (14th November 2020) - Schaefer, Andreas; Conradi, Lenard; Schneeberger, Yvonne; Reichenspurner, Hermann; Sandner, Sigrid; Tebbe, Ulrich; Nowak, Bernd; Stritzke, Jan; Kastrati, Adnan; Schunkert, Heribert; Scheidt, Moritz von; ,
Abstract: OBJECTIVES: In this post hoc analysis of the Ticagrelor in coronary artery bypass grafting (CABG) trial, we aimed to analyse patients treated with CABG receiving either complete revascularization (CR) or incomplete revascularization (ICR) independent from random allocation to either ticagrelor or aspirin. METHODS: Of 1859 patients enrolled in the Ticagrelor in CABG trial, 1550 patients (83.4%) received CR and 309 patients (16.6%) ICR. Outcomes were evaluated regarding all-cause mortality, cardiovascular death, myocardial infarction (MI), repeat revascularization, stroke and bleeding within 12 months after CABG. RESULTS: Baseline parameters revealed significant differences regarding clinical presentation (stable angina pectoris: CR 68.9% vs ICR 71.2%, instable angina pectoris: 14.1% vs 7.8%, non-ST elevation MI: 17.0% vs 21.0%, P ˂ 0.01), lesion characteristics (chronic total occlusion: CR 91.3% vs ICR 96.8%, P ˂ 0.01), operative technique [off-pump coronary artery bypass surgery (OPCAB): CR 3.0% vs ICR 6.1%, P ˂ 0.01] and number of utilized grafts (total number of grafts: 2.69/patient vs 2.49/patient, P ˂ 0.001). ICR patients displayed a significantly increased risk of repeat revascularization [hazard ratio (HR) 1.91, 95% confidence interval (CI) 1.16–3.16; P < 0.01] and percutaneous coronary intervention (HR 1.95, 95% CI 1.13–3.35; P < 0.05) within 12 months after CABG. Higher risk for repeat revascularization in ICR patients was independent from random allocation to either ticagrelor or aspirin and persisted after adjustment for baseline imbalances. CONCLUSIONS: Patients with ICR presented more stable at the time of admission, but received less grafts, highly likely due to a higher rate of chronic total occlusion lesions and performed OPCAB. Although mortality presented no difference between groups, our results suggest that patients benefit from CR with regard to prevention of repeat revascularization. Abstract : According to international guidelines, coronary artery bypass grafting (CABG) is indicated in patients with coronary artery disease (CAD) with involvement of the proximal left anterior descending, in 1- and 2-vessel CAD and in patients with left main- or 3-vessel disease independent from Synergy between percutaneous coronary intervention (PCI) with TAXUS drug-eluting stent and Cardiac Surgery score [1, 2].